Respostas

A melhor resposta!
2014-05-24T11:49:12-03:00
Efetue a multiplicação:
      (2√7+3√2) .  (√7-2√7)                 fazer a distributiva (PASSO A PASSO)

2
√7.√7 - 2√7.2√7 + 3√2.√7 - 3√2.2√7 =

2
√7.7   -  2.2√7.7 + 3√2.7   - 3.2 √2.7 =
2√49    -    4√49   + 3√14    -  6√14 =       fatorar  √49|7       e     √14|2
 2.7      -    4.7                 - 3√14=                           7|7                 7|7
                                                                             1/                   1/
  14     -     28    - 3√14              √49 =√7.7 =√7² = 7  e          √14 =√2.7 = √14 

  - 14 - 3√14

 



1 5 1